Adsorpsi Ion Logam Tembaga Menggunakan Nano Zeolit Alam yang Diaktivasi - Yulianis, Yulianis; Mahidin, Mahidin; Muhammad, Syaifullah (Institution for Industrial Research and Standardization of Industry - Padang, 2017)
This study was aimed to find out the ability of natural zeolite coming from Blang Pidie, South West Aceh District, Aceh Province, Indonesia, which was applied as an adsorbent to adsorp heavy metal copper (CuÂ²âº) ions in aqueous solution. This research was conducted to enhance the performance of natural zeolite by downsizing it to nano particles, then activated physically and chemically using 0.05 M HCl, then calcined at temperature 350Â°C for 2 hours. Test of CuÂ²âº metal ion adsorption to nano natural zeolite after activation was done by batch method to determine the effect of contact time, weight of the adsorbent, pH, and initial concentration. The results showed that the optimum adsorption at the initial concentration 38.998 mg/L, weight adsorbent 1 gram, pH 6 during 120 minutes of the contact time with the percentage metal ion CuÂ²âº adsorption up to 99.86% and adsorption capacity 7.789 mg/g. Isothermal adsorption ressembled with the isotherms Freundlich with the RÂ² value of 0.9685, Freundlich constants (Kf) 111.99 mg/g and n value 0.986. The kinetic studies indicated that the adsorption of metal ions CuÂ²âº could be described by pseudo second order kinetic model with linear regression value 0.9997 and a constant value 0.121 min-1.ABSTRAKÂ Penelitian ini bertujuan untuk melihat kemampuan zeolit alam yang berasal dari Blang Pidie, Kabupaten Aceh Barat Daya, Provinsi Aceh, Indonesia yang diaplikasikan sebagai adsorben untuk menyerap ion logam berat tembaga (CuÂ²âº) dalam larutan. Penelitian dilakukan dengan peningkatan unjuk kerja zeolit alam melalui pengecilan ukuran sampai nano partikel, selanjutnya diaktivasi fisika dan aktivasi kimia menggunakan HCl 0,05 M kemudian dikalsinasi pada temperatur 350 oC selama 2 jam. Uji adsorpsi ion logam CuÂ²âº terhadap nano zeolit alam setelah aktivasi dilakukan dengan metode batch untuk menentukan pengaruh waktu kontak, berat adsorben, pH, dan konsentrasi awal. Hasil penelitian menunjukkan adsorpsi optimum pada konsentrasi awal 40 mg/L, berat adsorben 1 gram, pH 6 selama waktu kontak 120 menit dengan persen ion logam CuÂ²âº yang terserap sebesar 99,86% dan kapasitas adsorpsi sebesar 7,789 mg/g. Â Isotermal adsorpsi menyerupai isoterm Freundlich dengan nilai RÂ² 0,9685, konstanta Freundlich (Kf) sebesar 111,99 mg/g dan nilai n sebesar 0,986. Studi kinetika menunjukkan bahwa adsorpsi ion logam CuÂ²âº mengikuti model kinetika orde dua semu dengan nilai regresi linier 0,9997 dan nilai konstanta 0,121 min-1.